Renal tubular epithelial cell-derived BAFF expression mediates kidney damage and correlates with activity of proliferative lupus nephritis in mouse and men. (February 2018) - Schwarting, A; Relle, M; Meineck, M; Föhr, B; Triantafyllias, K; Weinmann, A; Roth, W; Weinmann-Menke, J
B-cell activating factor of the tumour necrosis factor family (BAFF) is a cytokine, mainly produced by hematopoietic cells (e.g. monocytes/macrophages, dendritic cells), indispensable for B-cell maturation. The BLISS studies have demonstrated that blocking BAFF by the human monoclonal antibody belimumab is a valuable therapeutic approach in patients with clinically and serologically active systemic lupus erythematosus (SLE). However, the defined sources of BAFF, which contributes to SLE, are still unclear. Recent findings show that BAFF expression is not restricted to myeloid cells. Since lupus nephritis is the main cause of morbidity and mortality for SLE patients, the aim of this study was to investigate whether renal tubular epithelial cells (TEC) are an important source of BAFF and thus may contribute to the pathogenesis and progression of SLE. We found BAFF expression both in cultured murine and human TEC. These results could be verified with in situ data from the kidney. Moreover, BAFF expression in the kidneys of lupus-prone MRL- Fas lpr mice correlated with disease activity, and BAFF expression on TEC in biopsies of patients with diffuse proliferative lupus nephritis showed a correlation with the histopathological activity index. In vitro functional assays revealed an autocrine loop of BAFF with its binding receptors on TEC, resulting in a strong induction of colony stimulating factor-1. Finally, we identified divergent effects of BAFF on TEC depending on the surrounding milieu ('inflammatory versus non-inflammatory'). Taken together, our findings indicate that renal-derived BAFF may play an important role in the pathophysiology of the systemic autoimmune disease SLE.